University teacher development courses in the Uk neoliberal higher education context - Iryna Kushnir; Lucy Spowart (University of Aberdeen, School of Education, 2021)
In this feature, we view the professional recognition of university teachers through Postgraduate Certificate (PGCert) training courses via the perspective of the neoliberal university approach. This perspective, and the lack of research into the developmental potential of such courses, necessitates a call for large-scale research into academics' perspectives on the teacher training they receive through PGCert courses. This would develop our understanding of the scope of teacher training courses and facilitate the sharing of best practice as well as identifying areas for improvement. This is particularly important in the rapidly shifting context of the current global pandemic which requires teachers to draw on a range of online pedagogies.